Remote Regio- and Stereocontrol by the Sulfinyl Group: Diels-Alder Reaction of Sulfinyl Dienols and 8,8-Dimethylnaphthalene-1,4,5(8h)-Trione - Caroli-Rezende, M; Almodovar-Fajardo, I (2013)
Diels-Alder cycloaddition of 8,8-dimethylnaphthalene-1,4,5(8H)-trione with diastereomeric hydroxysulfinyldienes proceeded with high yields and good ?-facial and regioselectivities. The hydroxysulfoxide moiety controls the regio- and stereoselectivities, through hydrogen bonds in the suggested transition state. © 2012 Elsevier Ltd. All rights reserved.